Pengaruh Pemberian Giberelin dan Berbagai Media Tanam Terhadap Perkecambahan dan Pertumbuhan Benih Pala (Myristica fragrans Houtt) - Arianto Arianto; Zainuddin Basri; Imam Wahyudi (Mitra Sains, 2018)
The aims of this experiment were to obtain a suitable combination of planting medium and gibberelline concentration for the germination and growth of nutmeg seeds; to obtain a suitable planting medium as well as gibberelline concentration for the germination and growth of nutmeg seeds. This experiment used Split Plot Design and was arranged in Completely Randomized Design. Two factors were tested, namely concentration of gibberelline and the type of planting media. Concentration of gibberelline was ploted as main plot, with three concentrations tested, namely 200 ppm, 250 ppm and 300 ppm. The types of planting media were ploted as subplot with three types of planting media tested, namely sand, coco peat and sawing peat. Therefore, there were nine treatment combinations which each treatment combination was repeated three times. Data was analysed by using analysis of variance and followed by HSD at 5%. Results of this experiment indicated that nutmeg seeds soaked into gibberelline solution and germinated in coco peat medium produced more root numbers and higher normal germination dry weight; and the highest number of roots as well as the highest normal germination dry weight were obtained when seeds were soaked into 250 ppm gibberelline and germinated in coco peat medium. The number of roots and dry weight of normal germination on such treatment combination were 10.67 roots and 2.01 g per germinating seed. Coco peat medium was better for the germination and growth of nutmeg seeds as indicated with the highest germination rate, growth rate, length of plumula, length of roots, total length of roots as well as the ratio of plumula length and root length. The soaking of seeds into gibberelline had a relatively similar effect on the germination and growth of nutmeg seeds, except if the seeds were soaked into 250 ppm gibberelline and germinated in coco peat medium which produced the highest number of roots and the highest normal germination dry wieght.